Locative prepositional predicates in English:pragmatic, semantic and cognitive motivations1 - Sosa Acevedo, Eulalia (Estudios Ingleses de la Universidad Complutense, 2005)
In the last decades of the twentieth century, lexicist approaches to word formation acknowledge some degree of autonomy between morphology and grammar (among others, Aronoff 1985 [1976]), Szymanek 1980, 1985, Di Sciullo and Williams 1987). Much in the same vein, the Model of Functional Grammar (Dik 19972 [19891]) first integrates the Lexicon as a specific component for the analysis of lexical structures. Functional Grammar (FG), however, centers mainly on the development of the Component of Rules (Predicate Formation Rules) that specifically accounts for word-formation processes associated with syntactic constructions (De Groot 1987). The main concern of this paper is to present an analysis of locative prefixation in English within the framework of the Functional Lexematic Model, first propounded by Martín Mingorance (1984, 1985a,b, 1990), and to demonstrate that this model alternatively provides an adequate framework for an autonomous description and interpretation of those processes of derivation in which syntax only constitutes one of the many factors involved in word formation.